2002
DOI: 10.1002/jcb.10308
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the spatiotemporal expression pattern and function of N‐Cadherin inhibit cellular condensation and chondrogenesis of limb mesenchymal cells in vitro

Abstract: Cartilage formation in the embryonic limb is presaged by a cellular condensation phase that is mediated by both cell-cell and cell-matrix interactions. N-Cadherin, a Ca(2+)-dependent cell-cell adhesion molecule, is expressed at higher levels in the condensing mesenchyme, followed by down-regulation upon chondrogenic differentiation, strongly suggesting a functional role in the cellular condensation process. To further examine the role of N-cadherin, we have generated expression constructs of wild type and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 77 publications
(124 reference statements)
7
89
0
Order By: Relevance
“…Therefore, the diminishing effect of the coupled cadherin peptides was potentially a concomitant consequence of decreasing N-cadherin density on hMSCs with chondrogenesis. In fact, persistent expression of N-cadherin via viral transfection in limb mesenchymal cell culture had an inhibitory effect on chondrogenesis, possibly due to prolonged maintenance of increased cellcell adhesiveness, stressing the importance of precise temporal presentation of N-cadherin (21). Moreover, the encapsulated hMSCs elaborate and deposit increasing amounts of cartilage matrix with culture, which could block interactions with the peptide with time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the diminishing effect of the coupled cadherin peptides was potentially a concomitant consequence of decreasing N-cadherin density on hMSCs with chondrogenesis. In fact, persistent expression of N-cadherin via viral transfection in limb mesenchymal cell culture had an inhibitory effect on chondrogenesis, possibly due to prolonged maintenance of increased cellcell adhesiveness, stressing the importance of precise temporal presentation of N-cadherin (21). Moreover, the encapsulated hMSCs elaborate and deposit increasing amounts of cartilage matrix with culture, which could block interactions with the peptide with time.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the expression of the deletion mutant form of N-cadherin, which lacks either the extracellular homotypic interaction domains or the intracellular β-catenin binding site, results in decreased cellular condensation and impaired chondrogenesis (21,22). These findings suggest that both extracellular homotypic interaction and intracellular interaction with the catenin complex are essential for proper N-cadherin signaling (23).…”
mentioning
confidence: 99%
“…A region of interest (ROI) was selected around the thresholded aggregate using the wand tool, and ROI area plotted against aggregate age. The development and strength of aggregate physical integrity (through cell-cell adhesion) was determined by sedimentation analysis (Coakley et al, 2004;Edwards et al, 2007). Ultrasound was terminated following aggregate formation which led to sedimentation onto the USWT surface.…”
Section: Aggregate Image Analysismentioning
confidence: 99%
“…Chondrogenesis is a multi-step developmental process leading to the formation of skeletal tissues such as cartilage (reviewed in Delise et al, 2000 andShimizu et al, 2007). Mesenchymal cells in the developing limb bud deposit extracellular matrix, form tightly-packed condensations, then differentiate into chondrocytes, proliferate and mature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation